Phenol Is the Initial Product Formed during Growth and Degradation of Bromobenzene by Tropical Marine Yeast, Yarrowia lipolytica NCIM 3589 via an Early Dehalogenation Step - Vatsal, Aakanksha A.; Zinjarde, Smita S.; RaviKumar, Ameeta (Frontiers in Microbiology, 2017)
Bromobenzene (BrB), a hydrophobic, recalcitrant organic compoundis listed by environmental protection agencies as an environmental and marine pollutant having hepatotoxic, mutagenic, teratogenic and carcinogenic effects. The tropical marine yeast Yarrowia lipolytica 3589 was seen to grow aerobically on BrB and displayed a maximum growth rate (max) of 0.04 h-1. Furthermore, we also observed an increase in cell size and sedimentation velocity for the cells grown on BrB as compared to the glucose grown cells.The cells attached to the hydrophobic bromobenzene droplets through its hydrophobic and acid-base interactions. The BrB (0.5%, 47.6mM) was utilized by the cells with the release of a corresponding amount of bromide (12.87 mM) and yielded a cell mass of 1.86 g/L after showing 34% degradation in 96 h. Maximum dehalogenase activity of 16.16 U/mL was seen in the cell free supernatant after 24 h of growth. Identification of metabolites formed as a result of BrB degradation, namely, phenol, catechol, cis-cis muconic acid and carbon dioxide were determined by LC-MS and GC-MS. The initial attack on bromobenzene by Y. lipolytica cells lead to the transient accumulation of phenol as an early intermediate which is being reported for the first time. Degradation of phenol led to catechol which was degraded by the ortho- cleavage pathway forming cis-cismuconic acid and then to Krebs cycle intermediates eventually leading to CO2 production. The study shows that dehalogenation via an extracellular dehalogenase occurs prior to ring cleavage with phenol as the preliminary degradative compound being produced. The yeast was also able to grow on the degradative products phenol and catechol to varying degrees which would be of potential relevance in degradation and remediation of xenobiotic environmental bromoaromatic pollutants such asbromobenzene.